The Anthropocene! Beyond the natural? - UWSP - Rolston, Holmes, 1932-2025, speaker; University of Wisconsin Stevens Point, producer (Colorado State University. Libraries, 2017)
We are now entering the Anthropocene Epoch, so runs a recent enthusiastic claim. Humans can and ought go beyond the natural and powerfully engineer a better planet, managing for climate change, building new ecosystems for a more prosperous future. Perhaps the Anthropocene is inevitable. But: Rejoice? Accommodate? Accept it, alas? Perhaps the wiser, more ethical course is not so much beyond as keeping the natural in symbiosis with humans. Enter the Semi-Anthropocene! Basically Natural! Carefully!
"The Anthropocene! Beyond the Natural?" presentation at the University of Wisconsin Stevens Point, April 28, 2017. 1 hour, 6 minutes. Introduction by Chris Diehm, Philosophy, University of Wisconsin Stevens Point, 6 minutes. Rolston lecture 6-54 minutes. Questions and answers, 54 minutes.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental ethics; environmental policy; natural; natural resources; humans and nature; biosphere; technosphere; geoengineering; climate change; adaptation; wilderness; wild nature; planetary management; values; intrinsic value; Anthropocene Epoch